Psihosocialni dejavniki tveganja pri mladostnikih z epilepsijo - Kobilšek, Katja (Medicinski razgledi, 2005)
The aim of the study is to identify psychosocial risk factors among adolescents with epilepsy and compare them with those among healthy peers. We will also search for gender differences within studied group. The study sampleconsisted of 68 adolescents (34 males and 34 females) who are treated for epilepsy in Neurology department of Paediatric clinic Ljubljana. The age of these individuals ranged from 14 to 19 years when a structured questionnaire for assessing psychosocial risk factors was administered. Information on their physical and psychosocial medical history was obtained byreviewing medical documentation. The control group consisted of 4260 Slovenian high school students of the same age with no chronical medical condition. They filled in the same questionnaire in a study about psychosocialrisk factors (Tomori 1998). It is statistically significant that adolescents with epilepsy in comparison with healthy peers take less tranquillisers, drugs, and drink less alcohol. They get more emotional supportfrom their parents, and at the same time they more often come into conflict with them. The desire to create their own family is stronger among studied group. They feel less stress because of school and have less personal problems, which they find easy to discuss. They are also more frequently professionally treated. There is no significant difference between the groups concerning depression, self-esteem and suicidal behaviour. Statistically significant gender differences within studied group are: females are given less emotional support from parents, they are less frequently involved in sport and have more often suicidal thoughts than males. Adolescents with relatively well-controlled epilepsy in compariosn with healthy peers are at lower risk for the abuse of psychoactive substances, suicide; they have similar level of self-esteem, as well as less personal problems and lots of family support. (Abstract truncated at 2000 characters).
Keywords: Antikonvulzivi; Epilepsy; Anticonvulsants; Epilepsija; Kajenje; Social Behavior Disorders; Osebnostni testi; Personality Tests; Smoking; Socialno vedenje, motnje; Adolescenca; Adolescence; ankete; Risk Factors; Dejavniki tveganja; Substance Abuse; Self Concept; Samokoncept; Samomor, poskus; Suicide, Attempted; psihosocialni dejavniki; Questionnaires; mladostniki; socialno vedenje; samopodoba; depresija (medicina)